STRUCTURAL FEATURES OF RATS’ PAROTID SALIVARY GLANDS AFTER INTRODUCTION OF PLATIFILLINUM - Tsukanov, D.V. (World of Medicine and Biology, 2012)
Determination of basic structural changes is in-process conducted in the lobules of parotid salivary gland of rats after introduction of platifillinum. It is set, that its introduction influences on the processes of secret-extrusion. In the end-pieces seromucous cells are set, secretory granules of which on a structure were, and on a tinktorial properties - serosal. In the ductal system active carry of liquid flags were determined from a vascular rate and periductal interstitium to the lumens. The amount of plasma cells, macrofages and mast cells are insreased in an interstitium, that testifies to tension of local immune barrier.
Keywords: parotid salivary gland; platifillinum; rats